Amelioration of Paraquat-Induced Pulmonary Injury by Mesenchymal Stem Cells. Issue 9 (September 2013) - Tsai, Hsin-Lin; Chang, Jei-Wen; Yang, Hui-Wen; Chen, Chang-Wei; Yang, Chen-Chang; Yang, An-Hang; Liu, Chin-Su; Chin, Tai-Wai; Wei, Chou-Fu; Lee, Oscar K.
Acute paraquat (PQ) poisoning induces redox cycle and leads to fatal injury of lung. Clinical management is supportive in nature due to lack of effective antidote, and the mortality is very high. Mesenchymal stem cells (MSCs) process the properties of immunomodulation, anti-inflammatory, and antifibrotic effects and oxidative stress resistance. MSC transplantation may theoretically serve as an antidote in PQ intoxication. In this study, we examined the potential therapeutic effects of MSCs in PQ-induced lung injury. The degree of PQ toxicity in the rat type II pneumocyte cell line, L2, and MSCs was evaluated by examining cell viability, ultrastructural changes, and gene expression. L2 cells treated with 0.5 mM PQ were cocultured in the absence or presence of MSCs. For the in vivo study, adult male SD rats were administered an intraperitoneal injection of PQ (24 mg/kg body weight) and were divided into three groups: group I, control; group II, cyclophosphamide and methylprednisolone; group III, MSC transplantation 6 h after PQ exposure. MSCs were relatively resistant to PQ toxicity. Coculture with MSCs significantly inhibited PQ accumulation in L2 cells and upregulated the expression of antioxidative heme oxygenase 1 and metallothionein 1a genes, reversed epithelial-to-mesenchymal transition, and increased the viability of PQ-exposed L2 cells. Treatment with MSCs resulted in a significant reduction in severity of liver and renal function deterioration, alleviated lung injury, and prolonged the life span of rats. Altogether, our results suggest that MSCs possess antidote-like effect through multifactorial protection mechanism. The results of this preclinical study demonstrate that transplantation of MSCs may be a promising therapy and should be further validated clinically.